Colombian clays binary mixtures: physical changes due to thermal treatments - Santiago Betancourt Parra; Manuel Alejandro Domínguez Ortíz; Marcela Martinez Tejada (Dyna, 2020)
Usually, smectite clays, which are used for catalytic purposes, are subjected to chemical and thermochemical treatments to enhance their surface features. This research aims to analyze textural and structural features of the physical mixtures of two Colombian smectite clays at room temperature and after the treatment at 600°C, 800°C, and 1000°C. The physical mixtures of two Colombian clays were characterized by X-ray techniques, thermal analysis, and BET surface area to evaluate physical changes resulting from the three thermal treatments. The results showed the appearance of microstructural changes in basal spacing and other crystals minerals because of the loss of carbonates and alkaline oxides in the clays. Additionally, a dramatic reduction in surface area features was evidenced by the temperature increase. Simultaneously, an increase in the pore size was also observed because of the increase of the temperature treatment. The results reveal that the physical mixture is not an appropriate solution to enhance the textural properties of the Colombian clays for sorption or catalytic purposes.